2015
DOI: 10.1007/jhep11(2015)208
|View full text |Cite
|
Sign up to set email alerts
|

Neutrinoless double beta decay in type I+II seesaw models

Abstract: We study neutrinoless double beta decay in left-right symmetric extension of the standard model with type I and type II seesaw origin of neutrino masses. Due to the enhanced gauge symmetry as well as extended scalar sector, there are several new physics sources of neutrinoless double beta decay in this model. Ignoring the left-right gauge boson mixing and heavy-light neutrino mixing, we first compute the contributions to neutrinoless double beta decay for type I and type II dominant seesaw separately and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 86 publications
2
17
0
Order By: Relevance
“…To be more specific, the authors of [57] showed that for heaviest right handed neutrino mass as low as 400 GeV, the triplet scalars are allowed to be as low as around 800 GeV for right handed charged gauge boson mass 3.5 TeV. Here we extend both these works [56,57] by considering more general type I and type II seesaw terms with comparable strength and study their implications in LFV processes µ → 3e, µ → eγ and LNV process like 0νββ. Instead of considering any specific mass matrix structure for either type I or type II seesaw mass matrix, we consider a very general mass matrix for one of the seesaw terms.…”
Section: Jhep07(2016)022supporting
confidence: 54%
See 3 more Smart Citations
“…To be more specific, the authors of [57] showed that for heaviest right handed neutrino mass as low as 400 GeV, the triplet scalars are allowed to be as low as around 800 GeV for right handed charged gauge boson mass 3.5 TeV. Here we extend both these works [56,57] by considering more general type I and type II seesaw terms with comparable strength and study their implications in LFV processes µ → 3e, µ → eγ and LNV process like 0νββ. Instead of considering any specific mass matrix structure for either type I or type II seesaw mass matrix, we consider a very general mass matrix for one of the seesaw terms.…”
Section: Jhep07(2016)022supporting
confidence: 54%
“…More recently, the authors of [32,52,53] studied the new physics contributions to 0νββ process for TeV scale MLRSM with dominant type II seesaw. There have also been several works [54][55][56][57] where type I seesaw limit was also included into the computation of 0νββ in MLRSM. Some more detailed analyses incorporating left-right gauge mixing were discussed in the works [58][59][60][61][62].…”
Section: Jhep07(2016)022mentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent work [90] showed the possibility of lighter triplet scalars M i /M ∆ ≈ 0.5. In a subsequent work [91], it was shown that one can also have the possibility of M i /M ∆ > 1 if we consider the new physics contribution to the above-mentioned decay processes within a framework of equally dominant type I and type II seesaw, earlier studied in this context by [92]. Due to a different way of generating leading order neutrino mass in the present model, these bounds may however change as we discuss in the upcoming sections with further details.…”
Section: Jhep01(2017)072mentioning
confidence: 99%